On Fundamental Properties in Fuzzy Metric Space - Paudel, Gyan Prasad; Pahari, Narayan Prasad (Academic Journal of Mathematics Education, 2021)
Fuzzy metric spaces theory is important in mathematics, statistics, computer science, and other fields. In this paper fundamental characteristics of the fuzzy metric space are examined. The notions of fuzzy convergent sequence, fuzzy Cauchy sequence, fuzzy open ball, are reviewed with theorems associated with these concepts.